Pediatric reference intervals for 29 Ortho VITROS 5600 immunoassays using the CALIPER cohort of healthy children and adolescents - Higgins, Victoria; Fung, Angela W.S.; Chan, Man Khun; Macri, Joseph; Adeli, Khosrow (Clinical chemistry and laboratory medicine, 2018)
Accurate reference intervals (RIs) based on a healthy pediatric population are essential for pediatric test result interpretation. The CALIPER project has recruited a large healthy cohort and completed a series of a priori studies to address gaps in pediatric RIs. As immunoassays from different manufacturers for endocrine and special chemistry markers are not standardized and show marked intermethod differences, direct RI studies are needed for each major analytical platform. Here, we report age- and sex-specific pediatric RIs for 29 immunoassays on the Ortho Clinical Diagnostics (Ortho) VITROS® 5600 analyzer. Health information and blood samples were collected from healthy pediatric subjects. Using the Ortho VITROS 5600 Integrated System MicroWell Technology, 29 biomarkers were measured. Analyte concentrations were partitioned by age and sex according to the Harris and Boyd method. After removing outliers, age- and sex-specific RIs and corresponding 90% confidence intervals were calculated according to CLSI guidelines. All analytes required age partitioning except β-human chorionic gonadotropin (β-hCG), cancer antigen 15-3 (CA15-3), rubella immunoglobulin G (rubella IgG), and vitamin D. Several analytes including estradiol, progesterone, testosterone, follicle-stimulating hormone (FSH), luteinizing hormone (LH), free triiodothyronine (FT3), total triiodothyronine (TT3), total thyroxine (TT4), thyroid uptake, ferritin, intact parathyroid hormone (iPTH), total prostate-specific antigen (tPSA), free prostate-specific antigen (fPSA), cancer antigen 125 (CA125), creatine kinase MB (CK-MB), and myoglobin showed sex differences, observed mostly with the onset of puberty. Complex reference value trends were observed across the pediatric age range for several biomarkers examined on Ortho VITROS immunoassays. The availability of VITROS immunoassay RIs will enable accurate laboratory test interpretation and diagnosis for the pediatric population. As recommended by the CLSI EP28-A3c guidelines, implementation of these RIs should be validated for each laboratory's local pediatric population.